Embodiment and the Philosophy of Mind - Clark, Andy (Cambridge University Press, 1998)
Cognitive Science is in some sense the science of the mind. But an increasingly influential theme, in recent years, has been the role of the physical body, and of the local environment, in promoting adaptive success. No right-minded Cognitive Scientist, to be sure, ever claimed that body and world were completely irrelevant to the understanding of mind. But there was, nonetheless, an unmistakable tendency to marginalize such factors: to dwell on inner complexity whilst simplifying or ignoring the complex inner-outer interplays that characterize the bulk of basic biological problem-solving. This tendency was expressed in, for example, the development of planning algorithms that treated real-world action as merely a way of implementing solutions arrived at by pure cognition (more recent work, by contrast, allows such actions to play important computational and problem-solving roles). It was also expressed in David Marr’s depiction of the task of vision as the construction of a detailed three-dimensional image of the visual scene. For possession of such a rich inner model effectively allows the system to “throw away” the world and to focus current computational activity int he inner model alone.
Keywords: Philosophy